2017
DOI: 10.3390/w9070502
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluations of Three Silt Fence Practices Using a Full-Scale Testing Apparatus

Abstract: Erosion and sediment controls on construction sites minimize environmental impacts from sediment-laden stormwater runoff. Silt fence, a widely specified perimeter control practice on construction projects used to retain sediment on-site, has limited performance-based testing data. Silt fence failures and resultant sediment losses are often the result of structural failure. To better understand silt fence performance, researchers at the Auburn University-Erosion and Sediment Control Testing Facility (AU-ESCTF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…Based on the findings of Bugg et al ( 8 ), the Alabama Department of Transportation (ALDOT) standard reinforced silt fence ( 9 ) yielded no improvement in water quality and failed structurally when subjected to repeated 2-year, 24-h storm events. Thus, the Auburn University Erosion and Sediment Control Testing Facility (AU-ESCTF) research team were tasked with investigating alternative installation configurations that would enhance the overall performance of the standard ALDOT silt fence.…”
mentioning
confidence: 99%
“…Based on the findings of Bugg et al ( 8 ), the Alabama Department of Transportation (ALDOT) standard reinforced silt fence ( 9 ) yielded no improvement in water quality and failed structurally when subjected to repeated 2-year, 24-h storm events. Thus, the Auburn University Erosion and Sediment Control Testing Facility (AU-ESCTF) research team were tasked with investigating alternative installation configurations that would enhance the overall performance of the standard ALDOT silt fence.…”
mentioning
confidence: 99%
“…In order to minimize Sebeya river sediment loading rates, the present study strongly recommends the improvement of the existing soil erosion and sediment control measures for high effective performance. As indicated by different research findings, this study also propose to increase the implementation of soil erosion control measures including terraces [4], mulching [32], contour bunds [33], forestation and conservation tillage [34], various slopes stabilization measures, cover crops and vegetation [35], various riverbanks stabilization measures like riverbank stone revetment, grassed waterways [36] and specific sediment control measures such as buffer zones, sediment fences, sediment basin and check dams [37] [38] [39]. These measures have to be adopted basing on the specific area criteria in the Sebeya catchment like land slope, soil depth and other essential characteristics.…”
Section: Environmental Mitigation Measures For Adverse Impacts Of Sebmentioning
confidence: 99%
“…They tested the method for silt fence which retained an average of 90.5% by volume of sediment but silt fence did not show any evidence of filtering effect on water quality. In a follow-up study, Bugg et al (2017b) demonstrated the performance of three types of silt fences under full scale. They concluded that silt fences that are structurally strong would perform well to settle out particles through suspension, thus improving the water quality.…”
Section: Mccarthy Et Al (2017) Demonstrated a Microbial Sourcementioning
confidence: 99%